Protection of geographical indications and cross-border trade: A survey of legal and regulatory frameworks in East Africa - Saudin J. Mwakaje (John Wiley & Sons, Ltd, 2022)
Abstract Geographical indications (GIs), one of a subset of intellectual property rights (IPR), have recently assumed significant role in regulating variety of sectoral policies and national and regional, and international levels. Its relevance makes it one of the critical agenda in areas such as agriculture and international trade. Internationally, the articulation of GIs under TRIPs Agreement remains unclear and leaves policy and regulatory space for each country to choose their own path. The Continental Strategy for Geographical Indications in Africa—2018–2023 has introduced a new dimension about GIs. Legal instruments governing the East African Community (EAC) proffer a harmonized policy and regulatory framework for IPR as one of the means to attain the regional objectives. However, laws governing GIs in the partner states of EAC vary in terms of the nature and scope of protection and the underlying regulatory structures, resulting into heterogeneity in GIs protection in each country. Amid this regulatory dilemma, this paper examines the GIs laws in EAC by bringing to the fore the obtaining substantive and procedural differences amongst the partner states to EAC. The paper, among others, proposes a centralized regional approach for GIs protection to attain EAC's objective.
Keywords: Cross border trade, Eastern Africa perspectives, geographical indications, intellectual property rights